Penerapan Sistem Synchron CBE (Close Before Excitations ) Pada Diesel Generator Konvensional - Mohammad Suharto; Iwa Garniwa Mulyana K (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This article analyzes the performance of generator set (genset) synchronization systems using the Dead Bus Close Before Excitation (CBE) method compared to the live bus method, and evaluates the dynamic response of gensets through block load testing, PID tuning, and burning tests. The test results show that the Dead Bus CBE synchronization method achieves an average synchronization time of approximately 9 seconds, faster than the live bus method, which requires about 18 seconds, resulting in a time efficiency improvement of ±50%. This improvement directly impacts the reliability of the backup power system and reduces dependence on Uninterruptible Power Supply (UPS) battery capacity. Block load testing shows that the genset can handle 0–50% load with stable voltage and frequency responses, meeting the requirements of ISO 8528-5. In the 0–100% block load test, a voltage drop of up to –19% and a frequency decrease of –9% were observed, with a recovery time of approximately 5.5 seconds, classified as a conditional pass according to the standard. PID tuning results on the Digital Automatic Voltage Regulator (DAVR) and governor were proven to improve transient response, reduce voltage drop magnitude, and enhance system stability during synchronization and sudden load acceptance. Additionally, the burning test results indicate that the genset can operate continuously under high load with stable voltage, frequency, and thermal parameters without triggering protection faults. Overall, this study demonstrates that implementing Dead Bus CBE synchronization supported by proper PID tuning can improve the response speed, stability, and reliability of gensets as backup power sources for critical loads.